Yellowstriped Oakworm (suggested common name), Peigler's oakworm, Anisota peigleri Riotte (Insecta: Lepidoptera: Saturniidae) - David Serrano; John L. Foltz (EDIS)
The yellowstriped oakworm, Anisota peigleri, is an occasional pest on oak trees in the southeastern United States. In Florida, outbreak populations defoliated laurel, water and Shumard oaks in Gainesville from 1996 until 2001. Even when defoliation is not severe, the falling frass (droppings) and large numbers of caterpillars are a major concern for many homeowners. Frass commonly stains driveways, walkways, pool decks and other outdoor structures.